THE IMPORTANCE OF THE MAHALLA SYSTEM’S REFORMATIONS IN NEW UZBEKISTAN - Sadullayev Umidjon Shokir O’g’li (International Journal Of History And Political Sciences, 2023)
This article analyzes the reforms implemented in mahalla management in New Uzbekistan. Information is provided about the positions of assistant mayor, women's activist, and youth leader newly introduced in the mahalla system. The operation of the information system "temir daftar", "ayollar daftari", "yoshlar daftari" implemented in order to provide social support to the population was specially studied.